Identification of fungi isolated from astronaut nasal and pharyngeal smears and saliva. (16th February 2021) - Satoh, Kazuo; Yamazaki, Takashi; Furukawa, Satoshi; Mukai, Chiaki; Makimura, Koichi
Abstract: As part of a series of studies regarding the microbiota in manned space environments, we isolated the fungal strains from nasal and pharyngeal smears and saliva of 21 astronauts preflight, in‐flight, and postflight. On the ground, 120 strains from 43 genera of environmental fungi were isolated from the astronauts. The dominant fungal genera were Cladosporium, Penicillium, and Aspergillus . Only 18 strains from four genera were isolated from the astronauts inside the International Space Station. These fungi are currently thought to be harmless, but regular screening and cleaning are necessary to prevent fungus‐related health disorders.